Biological therapies in Crohn’s disease - Kaczor, Patryk; Lipa, Katarzyna; Jabłońska, Magdalena Julia; Leis, Kamil; Kałużny, Krystian; Gałązka, Przemysław (Journal of Education, Health and Sport, 2018)
Crohn’s disease is one of the chronic inflammatory diseases of the digestive tract. Pathophysiology of this disease involves the genetic and environmental factors, but the most important causative factor is anti-inflammatory reaction of the organism, which eventually leads to inflammatory changes, fibrosis and necrosis. Glucocorticosteroids are commonly used in therapy and may cause many negative side effects. Nowadays, new biological medicines are being tested, which are supposed to be an alternative method of treating Crohn’s disease. Infliximab, adalimumab, certolizumab pegol, natalizumab, etanerecept, vedolizumab and ustekinumab are the examples of those drugs, on which the research was already carried out. They lead to healing of the mucous membrane of the digestive tract, and thus to remission of the disease.